2021
DOI: 10.1152/ajpheart.00488.2020
|View full text |Cite
|
Sign up to set email alerts
|

G6PD activity contributes to the regulation of histone acetylation and gene expression in smooth muscle cells and to the pathogenesis of vascular diseases

Abstract: We aimed to determine: 1) the mechanism(s) that enable glucose-6-phosphate dehydrogenase (G6PD) to regulate serum response factor (SRF)- and myocardin (MYOCD)‑driven smooth muscle cell (SMC)-restricted gene expression, a process that aids in the differentiation of SMCs; and 2) whether G6PD-mediated metabolic reprogramming contributes to the pathogenesis of vascular diseases in metabolic syndrome (MetS). Inhibition of G6PD activity increased (>30%) expression of SMC-restricted genes and concurrently decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 69 publications
3
14
0
Order By: Relevance
“…After analyzing the existing CHIP-seq data for H3 modification, we found that H3K36me3, H3K79me2 and H3ac, which usually induce transcriptional activation of genes, interact with the promoter of G6PD in C2C12 myoblasts; after 60 h differentiation, the binding between G6PD promoter and H3K36me3 or H3K79me2 modification is decreased, and the binding between G6PD promoter and H3ac has almost disappeared. Dhagia et al found that G6PD activity contributes to the regulation of histone acetylation [31], and our CHIP result showed that histone acetylation is involved in regulating G6PD expression, indicating there are bidirectional regulation between G6PD and H3ac. BSP-Seq is regarded as the gold standard for DNA methylation detection [32], and our result showed that DNA methylation of G6PD promoter significantly increased after differentiation.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…After analyzing the existing CHIP-seq data for H3 modification, we found that H3K36me3, H3K79me2 and H3ac, which usually induce transcriptional activation of genes, interact with the promoter of G6PD in C2C12 myoblasts; after 60 h differentiation, the binding between G6PD promoter and H3K36me3 or H3K79me2 modification is decreased, and the binding between G6PD promoter and H3ac has almost disappeared. Dhagia et al found that G6PD activity contributes to the regulation of histone acetylation [31], and our CHIP result showed that histone acetylation is involved in regulating G6PD expression, indicating there are bidirectional regulation between G6PD and H3ac. BSP-Seq is regarded as the gold standard for DNA methylation detection [32], and our result showed that DNA methylation of G6PD promoter significantly increased after differentiation.…”
Section: Discussionsupporting
confidence: 66%
“…In previous studies, we found that G6PD is a target gene of miR-206, and miR-206 affects the C2C12 proliferation by down-regulating the protein expression of G6PD [33]. In addition, previous research has illustrated that G6PD deficiency is beneficial to MYH11 expression in smooth muscle cells [31]. Therefore, we first speculated that the downregulation of G6PD could affect the differentiation of skeletal muscle.…”
Section: Discussionmentioning
confidence: 97%
“…SMCs-restricted gene ( Myocd , Tagln , Myh11 , and Cnn1 ) expression maintains SMCs in a differentiated state; in contrast, downregulation of SMCs-restricted gene expression leads to SMCs cell dedifferentiation causing vascular remodeling. Pharmacological inhibition of G6PD or knockdown of G6PD promotes SMCs-restricted gene expression to maintain vascular function ( Dhagia et al, 2021 ). Therefore, G6PD maintains the dedifferentiated state of SMCs cells to avoid impaired vascular function.…”
Section: Role Of G6pd In Non-neoplastic Diseasesmentioning
confidence: 99%
“…Cardiovascular diseases Aldosterone has been found to inhibit G6PD activity, with G6PD inhibition reducing bioavailable nitric oxide, vascular reactivity, and the contractility of vascular smooth muscle cells, coronary arteries, and cardiomyocytes [14]. Additionally, G6PD activity modulates genes related to thrombosis, atherosclerosis, contractility, and blood vessel calcification [36], and mice with reduced G6PD activity develop spontaneous pulmonary hypertension with pulmonary artery and right heart remodeling [37]. However, it remains unclear if dysfunctional reactivity and contractility caused by G6PD def lead to a pathogenic phenotype in humans as G6PD def has been reported to be both cardioprotective and cardiodamaging [14,38].…”
Section: Glossarymentioning
confidence: 99%